Metformin modulates the unfolded protein responses, altering lifespan and health-promoting effects in UPR-activated worms. - Jerald Tan; Chutipong Chiamkunakorn; Kanpapat Boonchuay; Yiying Shi; Bart P Braeckman; Wichit Suthammarak (PLoS ONE)
Metformin has been demonstrated to extend lifespan in various model organisms, and its molecular effects are observed in the cytoplasm and multiple organelles, including mitochondria. However, its association with the unfolded protein response (UPR) and its impact on stress resistance and locomotion remain uncertain. In this study, metformin was found to exert differential influences on both UPRmt and UPRer. The correlation between metformin's lifespan-mediating effect and its interaction with UPRs was also inconsistent. We identified a metformin-mediated lifespan extension in wild-type C. elegans and in UPRmt-activated tomm-22 and cco-1 RNAi worms. Metformin suppressed the UPRmt without compromising the lifespan extension observed in tomm-22 worms. Conversely, metformin did not affect the UPRmt but extended the lifespan of long-lived cco-1 RNAi worms. Furthermore, we investigated the effects of metformin on UPRer-activated nematodes. We observed that metformin exhibited a slight increase in the UPRer in mdt-15 RNAi worms and failed to induce lifespan extension. Surprisingly, metformin appeared to mediate lifespan extension in tmem-131 RNAi worms while suppressing the UPRer. Notably, the correlation between thermotolerance, oxidative stress resistance, and the lifespan effects of metformin in UPR-activated worms was inconsistent. Activation of UPRs, but not metformin treatment, enhanced the locomotor phenotype of these worms.